(untitled) (International Journal of Communication Systems and Network Technologies, 2019)
In India most of the people’s livelihood is based on agriculture and it is their main occupation. Generally, the farmers plant the various crops based on the choice of people and they also use more fertilizers to plant them. Due to this, there is an enormous improvement in the usage of machine learning in the field of research and the different industries over the recent few years. This is the reason that we want to use machine learning extensively to build an advanced system in the field of agriculture and this is all done to improve the adaptability of the farmers in doing the agricultural practices. Over the years the research papers have just used only one attribute to showcase the idea about the usage of ML in the various systems. Further we want to increase the overall efficiency of the system and the results by adding more attributes to our ML based system, this indirectly can help us to figure out the patterns and yield more effective results based on prediction analysis. After which the system can be used to predict which crop can be grown in the different regions.